Albumin, Fibrinogen, Prothrombin and Antithrombin III Variations in Blood, Urines and Liver in Rat Nephrotic Syndrome (Heymann Nephritis) - Girot, R; Jaubert, F; Leon, M; Bellon, B; Aiach, M; Josso, F; Lepelletier, O; Beguin, S; Monnet, J-P (Thrombosis and Haemostasis, 1983)
Albumin, fibrinogen, prothrombin and antithrombin in (AT ID) variations have been studied in blood, urines and liver during an experimental nephrotic syndrome in rats (Heymann nephritis). A quantitative morphometric study (light microscopy) has been performed in the liver using an immunocytochemical technique – (PAP) method – to evaluate the protein synthesis by the number of protein-containing hepatocytes. Some sections were also studied by electron microscopy. The nephrotic animals were compared with control rats. In the blood of nephrotic rats, fibrinogen and prothrombin concentrations were increased and albumin and AT III concentrations were decreased. In the urines of nephrotic rats, albumin, prothrombin and AT III were lost, but no fibrinogen. The morphometric study in the liver has shown a significantly higher number of fibrinogen and prothrombin containing hepatocytes in nephrotic rats than in controls, suggesting an increased synthesis of these proteins; no change was observed concerning albumin and AT III between nephrotic and control animals. In electron microscopy, albumin was demonstrated in Golgi apparatus, proving that the peroxidase-positive cells are related to protein synthesis. These results show that the mechanisms of regulation of the protein synthesis during nephrotic syndrome are different from one protein to another and, particularly, that their blood level is not the only regulating factor for their synthesis.
Keywords: Fibrinogen; Prothrombin; Antithrombin III; (PAP) method; Nephrotic syndrome; Immunocytochemistry